Peningkatan Kemampuan Membedakan Bahasa Baku dan Tidak Baku Berdasarkan EYD: Studi Kasus Mahasiswa UIN Sumatera Utara - Khairunnisa, Riska; Fadhila, Puan; Budiman, Budiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The standard words are words that follow the recognized language rules in Indonesian. Spelling, conventional grammar, and common dictionary words are just some of the linguistic norms that can be found in standard words. The purpose of this research is to ensure how students use common and uncommon words. This research is qualitative and descriptive. Students majoring in Indonesian Language Education at the State Islamic University of North Sumatra participated in the research. Based on the research findings, most students majoring in Indonesian Language Education at the State Islamic University of North Sumatra are able to understand standard and non-standard words, while very few cannot.